Maternal deaths following nevirapine-based antiretroviral therapy - E Bera; D Naidoo; M Williams (AOSIS, 2012)
We report 2 cases illustrating that it is too simplistic to link nevirapine (NVP) toxicity exclusively to individuals with immune preservation. Not enough is known about the mechanism of hepatotoxicity or cutaneous eruption to predict these events. This type of hypersensitivity reaction occurs rarely among HIV-exposed infants taking NVP prophylaxis or antiretroviral therapy (ART)-experienced adults with complete plasma viral load suppression. Conversely, HIV-uninfected adults and ART-naive pregnant women appear to be disproportionately affected by the adverse effects of NVP.